RELEVANSI PENGUNGKAPAN TRANSAKSI PIHAK BERELASI. APAKAH PASAR MEMBERIKAN RESPON? - Dian Yuni Anggraeni (Universitas Teknokrat Indonesia, 2018)
Information is the result of a number of data processing. The relevance of information related to the usefulness of the information to support decision-making. One of the information in the financial statements which are popular is the information about transactions with related parties. This information is important because it can be used as a tool for management to report its best performance, which in fact is not (earnings management - opportunistic). This study sought to provide empirical evidence about the relevance of the extent of disclosure of related party transactions. Relevance proxies at the company's stock price. The results indicate that the related party transaction information which is proxied by the extent of disclosure of compensation of key management and reported presence of sales and purchases with related parties is relevant to the market Keywords: disclosure, related parties transaction, relevance.